Acute tonsillopharyngitis — view of infectiologist - A. A. Ploskireva (Лечащий Врач, 2021)
Approaches to the therapy of acute tonsillopharyngitis, depending on the etiology of the disease, were considered. Special attention was paid to topical remedies for treatment of acute tonsillopharyngitis. Clinical cases were given.